2012
DOI: 10.3347/kjp.2012.50.2.157
|View full text |Cite
|
Sign up to set email alerts
|

PCR for Diagnosis of Male Trichomonas vaginalis Infection with Chronic Prostatitis and Urethritis

Abstract: The aim of this study was to assess the usefulness of PCR for diagnosis of Trichomonas vaginalis infection among male patients with chronic recurrent prostatitis and urethritis. Between June 2001 and December 2003, a total of 33 patients visited the Department of Urology, Hanyang University Guri Hospital and were examined for T. vaginalis infection by PCR and culture in TYM medium. For the PCR, we used primers based on a repetitive sequence cloned from T. vaginalis (TV-E650). Voided bladder urine (VB1 and VB3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 13 publications
(16 reference statements)
2
47
0
Order By: Relevance
“…However, the method of detection used in these studies differs as well as the gene region analysed. A study done by Lee et al (2012) strongly supported the usefulness of PCR on urine samples for detecting T. vaginalis and further suggested that in clinical research settings in which vaginal specimens are not available and culture conditions are not feasible, urine-based PCR may be useful for the detection of trichomoniasis.…”
Section: Trichomoniasis Is a Common Sexually Transmitted Disease (Stdmentioning
confidence: 97%
“…However, the method of detection used in these studies differs as well as the gene region analysed. A study done by Lee et al (2012) strongly supported the usefulness of PCR on urine samples for detecting T. vaginalis and further suggested that in clinical research settings in which vaginal specimens are not available and culture conditions are not feasible, urine-based PCR may be useful for the detection of trichomoniasis.…”
Section: Trichomoniasis Is a Common Sexually Transmitted Disease (Stdmentioning
confidence: 97%
“…T. vaginalis infection causes vaginitis and cervicitis with profuse, frothy vaginal discharge and dysuria; pelvic inflammatory disease; preterm birth; and low-birth weight babies in women and urethral discharge (non-gonococcal urethritis), which is often asymptomatic and can be associated with prostatitis, epididymitis, and male factor infertility, in men. In addition, T. vaginalis infection has been implicated as a significant risk factor in the sexual transmission of human immunodeficiency virus (HIV) and other possible bacterial and viral STIs as well as of cervical cancer (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Because of all these reasons, there is a requirement for sensitive, time-independent, standard tests using noninvasive sampling for diagnosing trichomoniasis. In recent years, techniques using Polymerase chain reaction (PCR) have provided new approaches to increase the sensitivity as well as to use noninvasive body fluids such as urine (2,3,(12)(13)(14). In the present study, we aimed to detect T. vaginalis infection in urine samples obtained from males by performing nested PCR and to compare the results with those obtained using conventional methods.…”
Section: Introductionmentioning
confidence: 99%
“…With newer methods such as nucleic acid amplification [5,6] , the prevalence of Trichomonas and Chlamydia in men attending a sexually transmitted diseases clinic were shown to be as high as 17 and 19%, respectively [2] . In men with non-gonococcal urethritis, 19.9% were infected with Trichomonas [6] .…”
Section: Introductionmentioning
confidence: 99%
“…The surprisingly high rate of male urogenital infections with Trichomonas vaginalis ( T. vaginalis ), Chlamydia trachomatis ( C. trachomatis ), human papilloma virus (HPV), cytomegalovirus (CMV), herpes simplex virus (HSV), and Candida has only recently come into focus [1][2][3][4] , mainly because traditional diagnostic techniques such as urinalysis, smears, and serum testing have been shown to be inadequate [5] . With newer methods such as nucleic acid amplification [5,6] , the prevalence of Trichomonas and Chlamydia in men attending a sexually transmitted diseases clinic were shown to be as high as 17 and 19%, respectively [2] .…”
Section: Introductionmentioning
confidence: 99%